Principles of optical circuit engineering - Mentzer, Mark A. (Optical engineering (Marcel Dekker, Inc.), 1990)
Examines the devices, physical phenomena, and component technologies that facilitate diverse optical systems functions. Considers production and commercial aspects of microelectronic communication, computing, signal processing, and sensing systems. Presents design guidelines for optical circuits.